Observations on the Fine Structure of the Gastric Parietal Cell of the Rat - Lawn, A. M. (The Rockefeller University Press, 1960)
The structure of the rat parietal cell was examined by electron microscopy. The intercellular and intracellular canalculi are lined by microvilli which are more numerous and larger than those of other gastric cells. The numerous mitochondria have closely packed cristae and a dense matrix containing opaque particles. The cytoplasmic vacuoles typical of parietal cells are part of a network of smooth surfaced tubules and vacuoles (the endoplasmic reticulum) which is intimately associated with the mitochondria and probably connected with the lumen of the canaliculi. Only a few dense particles are found attached to the surface of these tubules. The structure of the parietal cell is compared with that of other cells whose function also is transport of inorganic ions and water. Evidence is presented supporting the hypothesis that parietal cells differentiate from a less structurally specialized cell in the neck region of the gastric gland.